The epic adventures of huggie & stick ebook - Daywalt, Drew (2018)
* "A surefire read-aloud for any wannabe hero." — Booklist (starred review) From Drew Daywalt, the #1 New York Times bestselling author of The Day the Crayons Quit , comes a hilarious buddy-comedy picture book starring a grouchy stuffed bunny and a happy-go-lucky stick. When super cheerful Stick and grumpy stuffed bunny Huggie get thrown from a backpack, the adventure is on! Together this odd couple survives encounters with sea-faring pirates, raging rhinos in Africa, sword-wielding royalty in Europe, stick-eating panda bears in Asia, sharks in Australia, hungry penguins in Antarctica, and piranhas in South America—all before finally making it home to North America. A fantastically funny read-aloud about two unlikely friends and their epic journey around the world.